Opening Up the Markets for Seed Trade in Africa - Keyser, John C. (World Bank, Washington, DC, 2014)
Despite its vast agriculture potential, Africa is increasingly dependent on food imports from the rest of the world to satisfy its consumption needs. Food output has not kept pace with population growth, and more than 80 percent of production gains since 1980 have come from the expansion of cropped areas rather than from greater productivity of areas already cultivated. This paper looks at the current requirements for seed trade in Africa, the obstacles, status of ongoing plans for regional harmonization, challenges of harmonization, and opportunities for near-term improvement. With Africa increasingly dependent on food imports, regional economic communities have been discussing harmonized seed policies for many years. While agreement on key regulations pertaining to variety release, seed certification, and phytosanitary control is now falling into place, improved farmer access to quality seeds are many years away due to capacity limitations and legal obstacles. Without relying on complex rules, experience elsewhere shows there are many simple options for improved seed trade that African governments can implement directly while continuing to work towards full harmonization.